Are Work Attitudes of Generations Myth or Real? Evidence from the United States and Turkey - Sait Gurbuz; Ihsan Aytekin (Istanbul Business Research (IBR), 2020)
Despite the increased attention paid to generational differences especially from practitioners and the popular press, systematic and empirical intergenerational research has been scarce, is largely North American centric, and lacks consistent results. The present study aimed to fill this gap by examining whether differences exist among generations in their key work and organizational attitudes, personal values, and work ethic values in the United States and Turkey. Survey data were gathered from 1019 employees (427 from the U.S. and 592 from Turkey). We found little evidence supporting substantive and significant generational differences or their association with key outcome variables. Furthermore, the U.S. originated classification of generations cannot be generalized to the Turkish business context.
Keywords: 650; Generational differences; Work attitudes; Work ethics; Cohorts